Peningkatan Efektivitas Pembelajaran Mata Kuliah Statistik Pendidikan melalui Penerapan Strategi Pembelajaran Aktif (Students as Teachers): Enhancing the Effectiveness of Educational Statistics Courses through the Implementation of the Active Learning Strategy (Students as Teachers) - Mundir Mundir (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2009)
Educational statistics is often perceived as a difficult subject by students, leading to low active participation, poor conceptual understanding, and a high incidence of copying assignments. This classroom action research aimed to improve the effectiveness of learning Educational Statistics through the implementation of the student as teacher active learning strategy. The study was conducted at STAIN Jember with 23 fourth-semester students of class K, employing two cycles consisting of planning, action, observation, and reflection. Data were collected through observation, interviews, lecturer and student notes, and the results of practice tests on difference tests (t-test and chi square). The findings showed a significant improvement: in cycle II, 86.96% of students (20 out of 23) achieved a minimum grade of B (≥70), exceeding the 75% success target, accompanied by increased active questioning, answering, and providing explanations. The research concludes that the student as teacher strategy effectively enhances the effectiveness of statistics learning. It is recommended that lecturers provide handouts, offer consultation sessions for students who will act as teachers, and conduct continuous collaborative observation and reflection. Pembelajaran statistik pendidikan sering dianggap sulit oleh mahasiswa, yang berdampak pada rendahnya partisipasi aktif dan pemahaman konseptual, serta tingginya perilaku menyalin tugas. Penelitian tindakan kelas ini bertujuan untuk meningkatkan efektivitas pembelajaran mata kuliah Statistik Pendidikan melalui penerapan strategi pembelajaran aktif student as teacher. Penelitian dilakukan di STAIN Jember pada mahasiswa semester IV Kelas K dengan subjek 23 mahasiswa, melalui dua siklus yang masing-masing terdiri atas perencanaan, tindakan, observasi, dan refleksi. Data dikumpulkan melalui observasi, wawancara, catatan dosen dan mahasiswa, serta hasil tes latihan soal uji beda (t-test dan chi square). Hasil penelitian menunjukkan peningkatan signifikan: pada siklus II, 86,96% mahasiswa (20 dari 23) memperoleh nilai minimal B (≥70), melampaui target keberhasilan 75%, disertai dengan meningkatnya keaktifan bertanya, menjawab, dan menambah keterangan. Penelitian ini menyimpulkan bahwa strategi student as teacher efektif meningkatkan efektivitas pembelajaran statistik. Direkomendasikan agar dosen menyediakan hand out, memberikan konsultasi kepada mahasiswa yang akan berperan sebagai guru, serta melakukan observasi dan refleksi bersama secara berkelanjutan.